Evaluation of postural stability of people with Parkinson’s disease with Biodex Balance System device - Wilczyński, Jacek; Kabała, Magdalena; Paprocki, Michał; Rychter, Paweł; Wilczyński, Igor (Journal of Education, Health and Sport, 2016)
Wilczyński Jacek, Kabała Magdalena, Paprocki Michał, Rychter Paweł, Wilczyński Igor. Evaluation of postural stability of people with Parkinson’s disease with Biodex Balance System device. Journal of Education, Health and Sport. 2016;6(10):365-376. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.163020 http://ojs.ukw.edu.pl/index.php/johs/article/view/3953 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.10.2016. Revised 02.10.2016. Accepted: 20.10.2016. Evaluation of postural stability of people with Parkinson’s disease with Biodex Balance System device Jacek Wilczyński1, Magdalena Kabała, Michał Paprocki, Paweł Rychter, Igor Wilczyński 1 Head: Department of Neurology, Neurological Rehabilitation and Kinesitherapy, Institute of Physiotherapy, Faculty of Medicine and Health Sciences, Jan Kochanowski University, Kielce, Al. IX Wieków Kielc, 25-317 Kielce, 19, Tel. 603-703-926, e-mail: jwilczyński@onet.pl dr hab. n. o k.f. prof. UJK Jacek Wilczyński, licencjat Magdalena Kabała, mgr Michał Paprocki, mgr Paweł Rychter, licencjat Igor Wilczyński Summary Parkinson’s disease is an incurable disease of the CNS of progressive and chronic course. Postural Stability of people with Parkinson’s is hindered what predisposes to falls. In a person standing seemingly motionless body performs small oscillatory movements caused by differences in antigravity muscle tension. This mechanism is called postural rocking and mobility associated with it is referred to as postural sway. The parameters of rocking are very sensitive indicator of balance control, and can be used to evaluate and detect pathological changes. The aim of the study was to evaluate the stability of posture of people with Parkinson’s disease on the basis of posturographic examination.The age range of the patients was from 52 to 85 years (mean 71.8 years). In terms of age the patients were divided into two groups. The first group consisted of 9 people to 75 years old, while the other of 8 people over 75 years old. The postural stability was assessed with Biodex Balance System. The study was performed at the Laboratory of Posturology at the Institute of Physiotherapy at UJK in Kielce. Although Mann-Whitney U test showed no significant differences in postural stability between the sexes, its lower values are reported for men. A standing position of the subjects was characterized by greater deviation in the sagittal plane than in the frontal plane (A/P>M/L) with a tendency to tilt backwards. There were better postural stability results in the younger group (group 1), up to 75 years old. The subjects in this group obtained significantly lower values of postural stability (t°=2.2744, p<0.05). Keywords: postural stability, Parkinson’s disease, Biodex Balance System Streszczenie Zaburzenia stabilności posturalnej są istotnym objawem choroby Parkinsona jako chronicznej niesprawności neurologicznej. Utrzymanie pionowej postawy ciała oraz jej kontrola są procesami wielopłaszczyznowymi. Postępujące i przewlekłe zmiany zanikowe oraz zwyrodnieniowe zmysłu wzroku, czucia głębokiego i układu przedsionkowego zaburzają stabilność postawy. Decydują o występowaniu skłonności do upadków, szczególnie przy gwałtownych ruchach głową. To z kolei prowadzi do osłabienia aktywności ruchowej oraz innych, związanych z tym konsekwencji. W badaniu wzięło udział 17 chorych w tym 12 (70,59%) kobiet i 5 (29,41%) mężczyzn. Grupa badawcza dobrana została spośród członków Stowarzyszenia Chorych na Parkinsona w Kielcach. Przedział wiekowy chorych wynosił od 52 do 85 lat (średnia 71,8 lat). Celem pracy była ocena stabilności postawy osób chorych na chorobę Parkinsona na postawie badania posturograficznego. Do oceny stabilności posturalnej zastosowano platformę Biodex Balance System. Badania wykonano w Laboratorium Posturologii w Instytucie Fizjoterapii na UJK w Kielcach. Choć test U Mann-Whitney nie wykazał istotnych różnic w stabilności posturalnej pomiędzy płciami to niższe jej wartości wystąpiły u mężczyzn. Postawę stojącą badanych charakteryzowały większe wychwiania w płaszczyźnie strzałkowej niż czołowej (A/P>M/L) z tendencją do odchylania się do tyłu. Zaobserwowano lepsze wyniki stabilności posturalnej w grupie osób młodszych (grupa 1) do 75 roku życia. Badani tej grupy uzyskali istotnie niższe wartości stabilności posturalnej (t°= 2,2744, p<0,05). Słowa kluczowe: stabilność posturalna, choroba Parkinsona, platforma Biodex Balance System